2017
DOI: 10.1016/j.annals.2017.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Fandom and risk perceptions of Olympic tourists

Abstract: Perceptions that travel to globally high profile events and destinations can be a risky activity has become more prevalent in recent years in response to various disastrous global incidents; some linked to major sports events such as the terrorist attacks at the Boston Marathon in April 2013 or at the Stade de France stadium in Paris in November 2015. In this current climate of perceived risk and uncertainty surrounding travel, and with specific relevance to mega sport events, this research note reviews the ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 8 publications
(4 reference statements)
0
19
0
1
Order By: Relevance
“…Secondly, and partially aligned to this previous observation, in terms of vulnerability to natural disasters, differing regions and host countries will be subject to variances in types, forms and frequency of natural hazards, such as earthquakes, volcanic eruptions, cyclones and/or tsunamis (see Miles, Gordon and Bang, 2017). Similarly, as the Rio 2016 Olympic and Paralympic Games highlighted with the zika virus, there are differing vulnerabilities to health hazards and communicable diseases (see Walters, Shipway, Miles and Aldrigui, 2017).…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…Secondly, and partially aligned to this previous observation, in terms of vulnerability to natural disasters, differing regions and host countries will be subject to variances in types, forms and frequency of natural hazards, such as earthquakes, volcanic eruptions, cyclones and/or tsunamis (see Miles, Gordon and Bang, 2017). Similarly, as the Rio 2016 Olympic and Paralympic Games highlighted with the zika virus, there are differing vulnerabilities to health hazards and communicable diseases (see Walters, Shipway, Miles and Aldrigui, 2017).…”
mentioning
confidence: 74%
“…Thirdly, it has also been previously identified that spectator perspectives on safety and security also feature in the attitudes of spectators on where to travel and when to attend (George and Swart, 2015;Taylor and Toohey, 2007;Qi, Gibson and Zhang, 2009;Walters et al, 2017). I would suggest that this relatively limited body of work would certainly merit a more comprehensive investigation in future years.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…In terms of vulnerability to natural disasters, differing regions and host countries are subject to variances in types, forms, and frequency of natural hazards, such as earthquakes, volcanic eruptions, cyclones, and/or tsunamis (see Miles, Gordon, & Bang, 2017). Additionally, as the Rio 2016 Olympic and Paralympic Games highlighted with the zika virus, there are differing vulnerabilities to health hazards and even communicable diseases (Shipway, 2018;Walters, Shipway, Miles, & Aldrigui, 2017). Moreover, in the developing world, man-made threats and risks such as crime rates, kidnapping, insurgencies, terrorism, or conflict may be more notable.…”
Section: Mega-ises and Resiliencementioning
confidence: 99%
“…Roehl and Fesenmaier, 1992;Floyd and Pennington-Gray, 2004;Dolnicar, 2005) and food (Mitchell and Boustani, 2015), but research in events is very limited and restricted to risk perceptions (e.g. Saadat et al, 2010;Schroeder et al, 2013;Walters et al, 2017). The purpose of this research was therefore to create a taxonomy of event participants based on risk and security perceptions.…”
Section: Introductionmentioning
confidence: 99%